2003
DOI: 10.1016/s1010-7940(03)00112-x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stent grafting for contained rupture of the descending thoracic aorta

Abstract: We report three cases of contained rupture of the descending thoracic aorta managed by endovascular stent grafting and discuss the possibility of managing this life-threatening complication in emergency, by endoluminal devices. Further experience is needed to specify the indications for aortic stenting in descendant thoracic aortic ruptures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…53,54 Retrospective series of patients with traumatic thoracic aortic disruptions treated with an endovascular approach have shown successful emergency repair of acute thoracic aortic disease. 55,56 Pratesi et al 57 reported 11 patients that were treated with stent grafts for acute rupture of the thoracic aorta; no neurologic deficits developed, and 30-day mortality was 9.1%. 57 Similarly, no procedure related paralysis was observed after TEVAR in 30 patients with TAT, and mortality was 6.6%.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Retrospective series of patients with traumatic thoracic aortic disruptions treated with an endovascular approach have shown successful emergency repair of acute thoracic aortic disease. 55,56 Pratesi et al 57 reported 11 patients that were treated with stent grafts for acute rupture of the thoracic aorta; no neurologic deficits developed, and 30-day mortality was 9.1%. 57 Similarly, no procedure related paralysis was observed after TEVAR in 30 patients with TAT, and mortality was 6.6%.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2 demonstrate a repair of Grade III traumatic aortic pseudoaneurysm via TEVAR). A variety of retrospective series of patients with traumatic aortic injuries treated with TEVAR have demonstrated successful outcomes [47,48]. Stoica and colleagues identified an early experience of 3 patients with acute rupture with successful TEVAR [48].…”
Section: Endovascular Approachmentioning
confidence: 99%
“…A variety of retrospective series of patients with traumatic aortic injuries treated with TEVAR have demonstrated successful outcomes [47,48]. Stoica and colleagues identified an early experience of 3 patients with acute rupture with successful TEVAR [48]. Pratesi and colleagues reported 11 patients treated with TEVAR successfully for acute aortic rupture with no neurologic deficits; the 30-day mortality was 9.1% [49].…”
Section: Endovascular Approachmentioning
confidence: 99%
“…[1][2][3][4] Aortic stenting can be applied to many patients ineligible for surgery, and it could be a preferred alternative to surgery under certain conditions. [5][6][7] However, the deployment of an endovascular device, as well as its incorporation in the vessel wall, is bound to confer changes in wall mechanics. 8,9 Impaired aortic wall mechanics have long been related to coronary artery disease (CAD) in patients with hypertension, renal disease, and, more recently, in apparently healthy populations.…”
Section: ¤ ¤mentioning
confidence: 99%